2007
DOI: 10.1177/0272431606294824
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Risk of Mothers and Children: The Role of Maternal HIV Infection

Abstract: Rates of mental health problems in mothers and children in families affected by maternal HIV as compared to those not affected by maternal HIV but living in similar inner-city, low-SES, primarily ethnic-minority neighborhoods were examined. In addition, correspondence between mother and child mental health was explored. Interviews were conducted with 220 mother/child dyads regarding symptoms of depression and anxiety. Participants included HIV-negative early adolescents (ages 10 through 14 years) and their mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
(67 reference statements)
6
45
0
Order By: Relevance
“…This result confirms the increased vulnerability to psychological distress among MLHIV (Benoit et al, 2014;Brackis-Cott, Mellins, Dolezal, & Spiegel, 2007;Catz, Gore-Felton, & McClure, 2002). This high prevalence cuts across sociodemographic characteristics and cannot be explained by low socioeconomic position, immigration status, or time since HIV diagnostic.…”
Section: Discussionsupporting
confidence: 72%
“…This result confirms the increased vulnerability to psychological distress among MLHIV (Benoit et al, 2014;Brackis-Cott, Mellins, Dolezal, & Spiegel, 2007;Catz, Gore-Felton, & McClure, 2002). This high prevalence cuts across sociodemographic characteristics and cannot be explained by low socioeconomic position, immigration status, or time since HIV diagnostic.…”
Section: Discussionsupporting
confidence: 72%
“…HIV-affected children were also significantly more likely to be viewed as less socially and cognitively competent. Their findings support a growing body of literature that suggests children of HIV-infected mothers are at increased risk for academic problems in school, depression, anxiety, and engaging in delinquent behaviors (e.g., Brackis-Cott, Mellins, Dolezal, & Spiegel, 2007;Fair, 2006;Forsyth, Damour, Nagler, & Adnopoz, 1996). One explanation for the increased risk of difficulties experienced by HIV-affected children was developed by Kotchick and colleagues (1997), who examined the effects of maternal HIV infection on parenting.…”
supporting
confidence: 62%
“…For example, while fewer babies were being diagnosed HIV-positive once mothers received antiretroviral medicines during pregnancy, such gains were offset by sharp increases in the number of children who live in families affected by HIV=AIDS (Nostlinger et al, 2004;Townsend et al, 2008;Whitmore et al, 2009). This outcome presented a conundrum for providers because care was available only to HIV-affected adults and children; children who were affected by HIV=AIDS comprised the large majority of dependents in such families but were excluded from receiving support services (Brackis-Cott, Mellins, Dolezal, & Spiegel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Elkington, Bauermeister, Brackis-Cott, Dolezal, and Mellins (2009) noted that such children typically live in impoverished households in risky neighborhoods where life is burdened by the prospect of parental illness and death. Such children are likely to suffer from depression, anxiety, social withdrawal, learning difficulties, and attention deficits (Brackis-Cott et al, 2007). Lee, Gortmaker, McIntosh, Hughes, and Oleske (2006) reported that children aged 5-11 years who were affected by HIV=AIDS had lower psychological functioning compared to their peers who were living with HIV=AIDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation